Perspectives From Systems Biology to Improve Knowledge of Leishmania Drug Resistance - Horácio, Elvira Cynthia Alves; Hickson, Jéssica; Murta, Silvane Maria Fonseca; Ruiz, Jeronimo Conceição; Nahum, Laila Alves (Frontiers in Cellular and Infection Microbiology, 2021)
Neglected Tropical Diseases include a broad range of pathogens, hosts, and vectors, which represent evolving complex systems. Leishmaniasis, caused by different Leishmania species and transmitted to humans by sandflies, are among such diseases. Leishmania and other Trypanosomatidae display some peculiar features, which make them a complex system to study. Leishmaniasis chemotherapy is limited due to high toxicity of available drugs, long term treatment protocols, and occurrence of drug resistant parasite strains. Systems biology studies the interactions and behavior of complex biological processes and may improve knowledge of Leishmania drug resistance. System-level studies to understand Leishmania biology have been challenging mainly because of its unusual molecular features. Networks integrating the biochemical and biological pathways involved in drug resistance have been reported in literature. Antioxidant defense enzymes have been identified as potential drug targets against leishmaniasis. These and other biomarkers might be studied from the perspective of systems biology and systems parasitology opening new frontiers for drug development and treatment of leishmaniasis and other diseases. Our main goals include: 1) Summarize current advances in Leishmania research focused on chemotherapy and drug resistance. 2) Share our viewpoint on the application of systems biology to Leishmania studies. 3) Provide insights and directions for future investigation.